Improvement of criteria significance determination / Kriterijų reikšmingumų nustatymo tobulinimas - Kaklauskas, A. (Journal of Civil Engineering and Management, 1996)
Having determined the significances of criteria by expert methods, we learn how much one of the criteria is more significant over another one. However, having determined by these methods the significances of technical-economical criteria (TEC) (they can be expressed in monetary or natural form: price and production costs of products, maintenance costs, construction time, labour expenditures, etc.), we do not find out everything we need. For instance, quantitative chracteristics of TEC in this case are not fully evaluated. Therefore a method should be developed enabling realistic and accurate assessment of these quantitative changes. The paper presents the method suggested by the author for significance determination of criteria, taking into account their quantitative and qualitative characteristics.Article in Lithuanian.First Published Online: 26 Jul 2012